HARQ scheme for sparse code multiple access based on network coding - Ke LAI; Jing LEI; Wei LIU; Lei WEN (Tongxin xuebao)
To fulfill the stringent reliability and throughput demand of the beyond-5G and the forthcoming 6G, a novel network coding (NC) based hybrid automatic retransmission request (HARQ) for low-density parity check (LDPC) coded SCMA was proposed.Two incorrectly received packets from different time slots were retransmitted by using NC principle under multi-user scenario.By doing so, the information came from two packets could be conveyed in one retransmission.Moreover, extra coding gain could be attained at the receiver.Furthermore, since the similarity between SCMA detector and LDPC decoder, and the one check node feature of NC decoder, a SCMA, LDPC and NC joint decoder based on message passing algorithm (MPA) was proposed.The proposed scheme could fully utilize the soft messages come from current and previous transmissions, and thus exploiting satisfied coding gain from NC.Simulation results show that the superiority of the proposed novel HARQ scheme for SCMA over the conventional HARQ on both throughput and reliability.